Pre-Marriage Course Based on Religious Moderation in Sadd Al-Żarī'ah Perspective - Anshor, Ahmad Muhtadi; Muttaqin, Muhammad Ngizzul (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2022)
This study intends to investigate pre-marital course practices based on religious moderation as an effort to oppose extremism. This is founded on the concept that the family is the smallest institution in a country, so it is very vital to develop a balanced attitude. The Ministry of Religious Affairs as the spearhead of this strategy has its own purpose in fulfilling this policy. One of the goals is how to genuinely avoid mafsadat early on. The concept of averting this mafsadat in the study of ushul fiqh and fiqh (Islamic law) is known as the sadd al-żarī'ah approach. This study is a literature review based on primary data from rules addressing the implementation of pre-marital courses. Meanwhile, secondary data were obtained from studies linked to the issue of this study. The content analysis method is used to derive findings. The findings in this study indicate that a pre-marital course focused on religious moderation as an effort to fight radicalism is a course model that provides training for future married couples to be moderate. Meanwhile, in the sadd al-żarī’ahperspective, a pre-marital course focused on religious moderation is a measure to prevent mafsadat.